The Right on Parenthood in the View of Buddhist Ethics - Wichai, Phra Chareonpong; Boonchuya, Phramaha Sathorn; Intapho, Phramaha Weeratis; Boonthong, Phramaha Supawat (Journal of MCU Buddhapanya Review, 2020)
A study on the right on parenthood in the view of Buddhist ethics has two objectives, one is to study and analyze social problems caused by the neglect of parental rights in various aspects such as intelligence, abandonment of children And conflicts or even family conflicts which leads to various problems as reflected. Another objective is to present the parental rights in accordance with Buddhist ethics. Methods of the study are 1) Conceptualization 2) Content collection 3) Analyze / classify data groups (Classification) which is Conducting the analysis and synthesis of the data under 3 types of thinking methods, which are 1) component classification Or distribute content 2) relationship ways of thinking Or thinking according to principles and aims. 3) How to think about the moral, blame and solution. The results of the study showing that the change in gender right values causes various social problems which are caused by the neglect of parental rights. The suggestion ways of Buddhist ethics scriptures that are the solution to these problems including the precepts principles as a prerequisite for the readiness of the parents. And the principle of rights of parenthood Point out to recognize the importance of parenthood. The principles set out the guidelines that should be followed between the children and the parents.